Analysis of Factors Affecting Poverty in Indonesia 2017-2022 - Nahor, Ratna Sari Dewi Banjar; Anggraini, Eka Dewi (Convergence: The Journal of Economic Development, 2024)
One of the indicators of the success of development is the level of poverty. This study aims to determine the effect of Economic Growth, Open Unemployment Rate, Inflation, Human Development Index, and Domestic Investment  on the poverty rate in 34 Provinces in Indonesia in 2017-2022. Data were obtained from the official website of Statistics Indonesia. This study used a quantitative method and data analysis used pane data regression with the selected mode Fix Effect Mode (FEM) with the help of Eviews9 software. The results showed that simultaneously economic growth, open unemployment rate, inflation, human development index, and domestic investment influence poverty levels in 34 provinces in Indonesia. Meanwhile, partially, Economic Growth, Open Unemployment Rate, Inflation, and Human Development Index significantly reduced poverty levels, while Domestic Investment did not significantly reduce poverty levels. For that reason, in order to reduce poverty levels in Indonesia, governments can focus on boosting economic growth and the human development index, job creation and suppressing inflation. The absorption of labor in the labor market will provide wages and increase income to meet daily needs which then reduce the poverty level. The decrease in inflation can increase people's purchasing power because people have adequate financial capacity to consume and meet their daily needs. The increase in the human development index will increase productivity, output, and remuneration for a company. Keywords :  Poverty, Economic Growth, Open Unemployment Rate , Inflation , Human Development Index, Domestic Investment. Abstrak Salah satu indikator keberhasilan pembangunan adalah tingkat kemiskinan. Studi ini bertujuan untuk menentukan pengaruh Pertumbuhan Ekonomi, Tingkat Pengangguran Terbuka, Inflasi, Indeks Pembangunan Manusia dan Investasi Dalam Negeri pada tingkat kemiskinan di 34 Provinsi di Indonesia pada 2017-2022. Data tersebut diperoleh dari situs resmi Statistics Indonesia. Studi ini menggunakan metode kuantitatif dan analisis data menggunakan regresi data panel dengan mode Fix Effect Mode (FEM) yang dipilih dengan bantuan perangkat lunak Eviews9. Hasil penelitian menunjukkan bahwa pertumbuhan ekonomi, tingkat pengangguran terbuka, inflasi, indeks perkembangan manusia, dan investasi domestik secara simultan mempengaruhi tingkat kemiskinan di 34 provinsi di Indonesia. Sementara itu, sebagian, Pertumbuhan Ekonomi, Tingkat Pengangguran Terbuka, Inflasi, dan Indeks Pembangunan Manusia secara signifikan mengurangi tingkat kemiskinan, sementara Investasi Domestik tidak secara substansial mengurangi tingkat Kemiskinan. Oleh karena itu, untuk mengurangi tingkat kemiskinan di Indonesia, pemerintah dapat fokus pada mendorong pertumbuhan ekonomi dan indeks pengembangan manusia, menciptakan pekerjaan dan menekan inflasi. Penyerapan tenaga kerja di pasar tenaga kerja akan memberikan upah dan meningkatkan pendapatan untuk memenuhi kebutuhan sehari-hari yang kemudian mengurangi tingkat kemiskinan. Penurunan inflasi dapat meningkatkan daya beli orang karena orang memiliki kapasitas keuangan yang memadai untuk mengkonsumsi dan memenuhi kebutuhan sehari-hari mereka. Peningkatan indeks pengembangan manusia akan meningkatkan produktivitas, output, dan remunerasi untuk sebuah perusahaan. Kata kunci : Kemiskinan, Pertumbuhan Ekonomi, Tingkat Pengangguran Terbuka, Inflasi, Manusia Indeks Pembangunan, Investasi domestik.